Thinking Process of X Science Students in Web Design using Polya - Ardymulya Iswardani; Nugroho Arif Sudibyo; Moh. Muhtarom; Muslimin (Proceeding of International Conference on Science, Health, And Technology, 2019)
Degree of thinking process affect student achievement. Measurement of the degree of thinking process with Polya is expected to obtain knowledge in the form of students thinking level abilities. Data collection of respondent used purposive sampling and snowball. The data then analyzed based on Polya. This study concluded that 10th-grade science students completely reach all four Polya.